Neuro-protective effect of rutin against Cisplatin-induced neurotoxic rat model - Mashal M. Almutairi; Wael A. Alanazi; Musaad A. Alshammari; Moureq Rashed Alotaibi; Ali R. Alhoshani; Salim Salah Al-Rejaie; Mohamed M. Hafez; Othman A. Al-Shabanah (BMC, 2017)
Abstract Background Cisplatin is widely used chemotherapeutic agent for cancer treatment with limited uses due to its neurotoxic side effect. The aim of this study was to determine the potential preventive effects of rutin on the brain of cisplatin- neurotoxic rat model. Methods Forty rats were divided into four groups. Group-1 (control group) was intra-peritoneal (IP) injected with 2.5 ml/kg saline. Group-2 (rutin group) was orally administrated 30 mg/kg rutin dissolved in water for 14 days. Group-3 (cisplatin group) was IP received 5 mg/kg cisplatin single dose. Group-4 (rutin and cisplatin group) was orally administrated 30 mg/kg rutin dissolved in water for 14 days with a single dose of 5 mg/kg cisplatin IP on day ten. Brain tissues from frontal cortex was used to extract RNA, the gene expression levels of paraoxonase-1 (PON-1), PON-2, PON-3, peroxisome proliferator-activated receptor delta (PPAR-δ), and glutathione peroxidase (GPx) was investigated by Real-time PCR. Results Cisplatin significantly decreased the expression levels of PON-1, PON-3, PPAR-δ and GPX whereas significantly increased PON-2 expression levels. Co-administration of Rutin prevented the cisplatin-induced toxicity by restoring the alteration in the studied genes to normal values as in the control group. Conclusion This study showed that Rutin has neuroprotective effect and reduces cisplatin- neurotoxicity with possible mechanism via the antioxidant pathway.